Sea otters : a survival story - Groc, Isabelle (Orca wild., 2020)
Examines the role of sea otters in the Pacific Ocean as a keystone species, one which was nearly hunted to extinction in the fur trade of the eighteenth and nineteenth centuries. Includes photographs and photojournalist pieces on men and women in the field working to help sea otter population numbers rebound. Includes a glossary.